Livestock policies in Son La Province, Vietnam - a review - Dung, Pham Van; Savelli, Adam; Mai Thanh Tu; Hung Nguyen-Viet; Le Thi Thanh Huyen; Douxchamps, Sabine (Bioversity International and the International Center for Tropical Agriculture, 2020)
Since the market-oriented Doi Moi reforms of the 1980s and 1990s, Vietnam’s livestock sector has experienced rapid growth. Although policies have been implemented at the national and provincial levels to guide this growth in a sustainable manner, blind spots and implementation gaps remain. Through a review of policy documents, grey literature, peer-reviewed journal articles, and key informant interviews, this research seeks to summarize livestock-related policies at the national and provincial levels in Son La, Vietnam. Policies related to land-use, livestock feed, animal breed development, credit provision, epidemiology, agricultural extensions services, public investment, and sectoral master planning are examined. Based on this review, the authors recommend greater support for smaller actors in Son La’s livestock value chains, mainly in the form of additional research and development, increased credit provision and agricultural insurance, improved agricultural extension services, and strengthened local processing capacity. These policy interventions and investments, among others, will be critical to achieving the government’s ambitious livestock production targets over the coming decade. Notably, more robust public intervention and support is required to unlock this growth. Additional funding for locallevel Ministry of Agriculture and Rural Development (MARD) initiatives and improved coordination between its national and provincial offices will be a key determinant in achieving sustainable intensification in Son La’s livestock sector.